Genetic and epigenetic profiling indicates the proximal tubule origin of renal cancers in end‐stage renal disease. Issue 11 (18th September 2020) - Ishihara, Hiroki; Yamashita, Satoshi; Liu, Yu‐Yu; Hattori, Naoko; El‐Omar, Omar; Ikeda, Takashi; Fukuda, Hironori; Yoshida, Kazuhiko; Takagi, Toshio; Taneda, Sekiko; Kondo, Tsunenori; Nagashima, Yoji; et al.
Abstract: End‐stage renal disease (ESRD) patients on dialysis therapy have a higher incidence of renal cell carcinomas (RCCs), which consist of 2 major histopathological types: clear‐cell RCCs (ESRD‐ccRCCs) and acquired cystic disease (ACD)‐associated RCCs. However, their genetic and epigenetic alterations are still poorly understood. Here, we investigated somatic mutations, copy number alterations (CNAs), and DNA methylation profiles in 9 ESRD‐ccRCCs and 7 ACD‐associated RCCs to identify their molecular alterations and cellular origins. Targeted sequencing of 409 cancer‐related genes, including VHL, PBRM1, SETD2, BAP1, KDM5C, MET, KMT2C ( MLL3 ), and TP53, showed ESRD‐ccRCCs harbored frequent VHL mutations, while ACD‐associated RCCs did not. CNA analysis showed that ESRD‐ccRCCs had a frequent loss of chromosome 3p while ACD‐associated RCCs had a gain of chromosome 16. Beadarray methylation analysis showed that ESRD‐ccRCCs had methylation profiles similar to those of sporadic ccRCCs, while ACD‐associated RCCs had profiles similar to those of papillary RCCs. Expression analysis of genes whose expression levels are characteristic to individual segments of a nephron showed that ESRD‐ccRCCs and ACD‐associated RCCs had high expression of proximal tubule cell marker genes, while chromophobe RCCs had high expression of distal tubule cell/collecting duct cell marker genes. In conclusion, ESRD‐ccRCCs and ACD‐associated RCCs had mutation and methylation profiles similar to those of sporadic ccRCCs and papillary RCCs, respectively, and these 2 histopathological types of RCCs were indicated to have originated from proximal tubule cells of the nephron. Abstract : We revealed that 2 major histopathological types of renal cell carcinomas (RCCs) that arise in end‐stage renal disease (ESRD), namely clear‐cell RCCs (ESRD‐ccRCCs) and acquired cystic disease (ACD)‐associated RCCs, had mutation and methylation profiles similar to those of sporadic ccRCCs and papillary RCCs, respectively. This finding indicates that these 2 histopathological types of RCCs arising in ESRD originated from proximal tubule cells of a nephron.